2021
DOI: 10.1001/jamanetworkopen.2021.38238
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of State Vaccine Incentive Lottery Programs and Uptake of COVID-19 Vaccinations in the United States

Abstract: Key Points Question Have vaccine lottery programs in the United States been associated with increases in the COVID-19 vaccination rate? Findings This cross-sectional study of 403 714 adult participants in the Household Pulse Survey and state daily vaccination rates found that vaccine lottery programs were associated with an increase in COVID-19 vaccination rates overall and in some states but not in others. Meaning These findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 48 publications
2
47
0
Order By: Relevance
“…The results found were interesting and confirm the expected significant heterogeneity in treatment effects (Dubé et al (2014) Acharya and Dhakal (2021)), affirming that there are differences in treatment effects between counties in the same states, suggesting that the social characteristics that determine this heterogeneity should be studied. Ohio, Washington, Kentucky, West Virginia, Illinois and Nevada outperformed other states obtaining positive and significant results, while the other states obtain no to negative results.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The results found were interesting and confirm the expected significant heterogeneity in treatment effects (Dubé et al (2014) Acharya and Dhakal (2021)), affirming that there are differences in treatment effects between counties in the same states, suggesting that the social characteristics that determine this heterogeneity should be studied. Ohio, Washington, Kentucky, West Virginia, Illinois and Nevada outperformed other states obtaining positive and significant results, while the other states obtain no to negative results.…”
Section: Discussionsupporting
confidence: 54%
“…Since the announcement by the governor of Ohio, several governors have introduced their vaccine lotteries, creating a natural phenomenon of policy mimicking. While there is some consensus over the positive results of conditional cash lotteries in Ohio (Barber and West (2021), Acharya and Dhakal (2021)); very early evaluations from Arkansas Gov. Hutchinson head in different directions, the lotteries have not been extended because of the population's scarce involvement the policy.…”
Section: Disentangling Treatment Effectsmentioning
confidence: 99%
“…The grief and physical isolation during the COVID-19 pandemic exacerbated the psychological distress to an unprecedented level, raising alarms about the mental health conditions across the country. At the same time, the government undertook multiple measures in containing the spread of the virus including the declaration of a nationwide emergency and the implementation of stay-in-home policies that actively discouraged in-person medical visits for non-life-threatening conditions [ 13 ] and mass vaccinations [ 14 ]. With the enactment of the CARES act in March 2020, healthcare providers responded to this disruption in healthcare service by expanding telehealth coverage, aimed at substituting the reduction in in-person visits by telephone and video-based engagements with the patients.…”
Section: Introductionmentioning
confidence: 99%
“…Campos-Mercade et al 3 found that a moderate ($24) cash incentive increased COVID-19 vaccine uptake by 4.2 percentage points, whereas Wong et al 4 found that $25 was associated with slower decline of vaccination uptake. Acharya and Dhakal 5 found that large but uncertain incentives (lottery programs) across 11 states had mixed success.…”
Section: Introductionmentioning
confidence: 99%